2007
DOI: 10.1021/tx7003294
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Transcriptional Networks Induced by Exposure to 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: The environmental contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) serves as a prototype for a range of environmental toxicants and as a pharmacologic probe to study signal transduction by the aryl hydrocarbon receptor (AHR). Despite a detailed understanding of how TCDD exposure leads to the transcriptional up-regulation of cytochrome P450-dependent monooxygenases, we know little about how compounds like TCDD lead to a variety of AHR-dependent toxic endpoints such as liver pathology, terata, thymic invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Our previous results indicated that the mouse uterus accumulates TCDD to a similar level as the liver, which was higher than other tissues (Li et al, 2006). A molecular marker of AhR activation is Cyp1a2 (Hayes et al, 2007), which can sequestrate TCDD in tissues and is a critical factor in TCDD accumulation (Grassman et al, 1998;Miller, 1997;Hakk et al, 2009). The Cyp1a2 expression in the uterus may indicate a possible functional alteration and TCDD accumulation, as a marker of uterine malfunction and deposit.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous results indicated that the mouse uterus accumulates TCDD to a similar level as the liver, which was higher than other tissues (Li et al, 2006). A molecular marker of AhR activation is Cyp1a2 (Hayes et al, 2007), which can sequestrate TCDD in tissues and is a critical factor in TCDD accumulation (Grassman et al, 1998;Miller, 1997;Hakk et al, 2009). The Cyp1a2 expression in the uterus may indicate a possible functional alteration and TCDD accumulation, as a marker of uterine malfunction and deposit.…”
Section: Discussionmentioning
confidence: 97%
“…Quality and quantity of RNA were assessed on an Agilent 2100 Bioanalyzer (Agilent, Palo Alto, CA) using the RNA Nano Labchip. Similar as described previously (27), total RNA was reverse-transcribed into cDNA using specific primers containing a Cy-3 “capture sequence.” The cDNA was then hybridized onto a microarray for eighteen hours. The arrays were washed according to the manufacturer’s specifications.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies, designed to examine gene expression after AhR activation by an exogenous ligand, have repeatedly reported AhR-dependent transcriptional regulation of CYP1 genes associated with AhR's traditional role in the adaptive metabolism of xenobiotics (Nebert et al, 2004). More recently, microarray studies have proved to be paramount in identifying expression changes in TCDD-dependent gene batteries associated with the toxicities observed after AhR activation (Vezina et al, 2004;Boverhof et al, 2005;Hayes et al, 2007;Lo et al, 2011). AhR activation by exogenous ligands is associated with several toxicities affecting multiple tissues and biologic systems, including hepatotoxicity, cardiotoxicity, teratogenesis, endocrine disruption, and diabetes (Denison et al, 2011).…”
Section: Introductionmentioning
confidence: 99%